Identities among actin-encoding cDNAs of the Nile tilapia (Oreochromis niloticus) and other eukaryote species revealed by nucleotide and amino acid sequence analyses - Poletto, Andréia B. [UNESP]; Wasko, Adriane Pinto [UNESP]; Oliveira, Claudio [UNESP]; Azevedo, Alexandre [UNESP]; Carvalho, Robson F. [UNESP]; Silva, Maeli Dal Pai [UNESP]; Foresti, Fausto [UNESP]; Martins, Cesar [UNESP] (Sociedade Brasileira de Genética, 2008)
Actin-encoding cDNAs of Nile tilapia (Oreochromis niloticus) were isolated by RT-PCR using total RNA samples of different tissues and further characterized by nucleotide sequencing and in silico amino acid (aa) sequence analysis. Comparisons among the actin gene sequences of O. niloticus and those of other species evidenced that the isolated genes present a high similarity to other fish and other vertebrate actin genes. The highest nucleotide resemblance was observed between O. niloticus and O. mossambicus a-actin and b-actin genes. Analysis of the predicted aa sequences revealed two distinct types of cytoplasmic actins, one cardiac muscle actin type and one skeletal muscle actin type that were expressed in different tissues of Nile tilapia. The evolutionary relationships between the Nile tilapia actin genes and diverse other organisms is discussed.
Keywords: actin; expression pattern; Nile tilapia; Oreochromis niloticus